Two ethics, double morality - Majcherek, Janusz A. (Studia Ecologiae et Bioethicae, 2016)
According to the declaration made by many theoreticians of environmental ethics, their purpose is to do moral extension, i.e., to expand moral duties and standards to non-human living entities. If it means including the biosphere into the same moral normative system as is valid in anthroposphere, such a declaration is in fact not realized. Environmental ethics offers normative systems not only different, but often contradictory to human ethics. These differences and sometimes contradictions make a great challenge for a moral subject, always a human being. The question is if it is possible to be equally obedient to such different or even contradictory rules, and construct a double or even dual conscience, according to such double morality.